Polygamy and its Effect on Mental Health - Ertan Yilmaz; Lut Tamam; Ufuk Bal (Psikiyatride Güncel Yaklaşımlar, 2015)
Polygamy is a form of marriage in which more than one gender involved in its institution. It's seen all around the world, being especially common in the Middle East, South Asia and Africa. Polygamy is a multidisciplinary subject with social, cultural, economic, political and religious aspects. Polygamy mainly has various effects on mental health of women and children. The objective of this article is to accomplish a review on the prevalence and causes of polygamy, studies conducted by various disciplines about the features of polygamic marriage institution and its effect on mental health. [Psikiyatride Guncel Yaklasimlar - Current Approaches in Psychiatry 2015; 7(2): 221-228]